2014
DOI: 10.1159/000357471
|View full text |Cite
|
Sign up to set email alerts
|

A New Scoring Method of the Mini-Mental Status Examination to Screen for Dementia

Abstract: Background: Although the Mini-Mental Status Examination (MMSE) is the most widely used screening instrument for dementia, it has several limitations. Methods: We developed and validated a new scoring method of the MMSE, namely the short form of the MMSE (MMSE-S). Results: The MMSE-S was more robust to demographic influences than the MMSE. The influence of education, in particular, was smaller in the MMSE-S compared to the MMSE (p < 0.01). The diagnostic accuracy of the MMSE-S for very mild to mild dementia was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Our results correspond to findings from other studies that showed the negative impact of age, the positive impact of education, and no impact with regard to gender on MMSE scores [8,21,22,23,24,25]. There was one study that found a significant gender affect [7]. Only one study did not find sociodemographic relationships with MMSE scores [26].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results correspond to findings from other studies that showed the negative impact of age, the positive impact of education, and no impact with regard to gender on MMSE scores [8,21,22,23,24,25]. There was one study that found a significant gender affect [7]. Only one study did not find sociodemographic relationships with MMSE scores [26].…”
Section: Discussionsupporting
confidence: 90%
“…Our mean score on the MMSE (28 ± 2) in the Czech Republic was similar to those in other elderly Czechs (29 ± 1), in the USA (29 ± 1; 28 ± 2), Canada (27 ± 2), Australia (27 ± 4), Japan (29 ± 2; 28 ± 2), Korea (27 ± 2; 26 ± 3), Singapore (27 ± 3; 28 ± 2), Slovenia (27 ± 2), Croatia (27 ± 3), and Italy (27 ± 2) [4,6,7,21,23,24,25,26,27,28,29,30]. Therefore, performance in NOS appears to be cross-culturally independent and shows a ceiling effect (the test is ‘too easy').…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation